The making and breaking of kinetic empire: mobility, communication and political change in the eastern Mediterranean, c. 900-1100 CE - Holmes, C (Cambridge University Press, 2022)
This paper applies the concept of ‘kinetic empire’ to the eastern Mediterranean world in the tenth and eleventh centuries. The term ‘kinetic empire’ is borrowed from Hämäläinen's analysis of the eighteenth- and nineteenth-century north American Comanche Empire. It refers to the way in which trans- and supra-regional power could be created, expressed and enforced through mobile means. The article focuses primarily on the role of mobility in the expansion of the Byzantine Empire between c. 900 and 1050, but also makes comparison with the contemporaneous Fatimid caliphate and other regional polities which we might usually regard as sedentary states. Recovering the role of the kinetic not only extends our understanding of the modalities of power in this crucial region of the medieval world, it also allows us to question the nature and degree of transformation wrought by mobile newcomers, such as Normans, crusaders and Turks in the later decades of the eleventh century. In this sense of developing and exploring concepts useful for the study of the transregional in premodernity and questioning standard periodisations, this article is also a practical exercise in medieval global history.